Respons Pertumbuhan Tebu (Sacharum officinarum L.) terhadap Pengolahan Tanah pada Dua Kondisi Drainase - M.Maulana Rasyid Lubis; Lisa Mawarni; Yusuf Husni (Jurnal Agroekoteknologi, 2015)
Drainage and land cultivation be determaining factor for optimal production of sugar cane. For thatpurpose, this research aimed to know response growth of of sugar cane (Sacharum officinarum L.)to land cultivation on some drainage condition. This research was conducted in Plantation Field ofPT Perkebunan Nusantara II Kebun Sampali, Deli Serdang on July 2013 – January 2014, used splitplot design with two factor are; drainage (good and bad drainage), and land cultivation (maximumand minimum land cultivation). Parameter observed are plant height, stem diameter, number ofinternodes, and number of stem.The result showed that drainage significantly affect on plant height1-6 months after planting (MAP), stem diameter 1, 2, 5 dan 6 MAP, and number of internodes 1-6MAP. Land cultivatin significantly affect on plant height 1-6 MAP, stem diameter 1, 2, 3, 5 dan 6MAP, number of internodes 1-6 MAP, and number of stem 6 MAP. Interaction between two factorssignificantly affect on plant height 1-6 months after planting (MAP), stem diameter 1, 2, 5 dan 6MAP, and number of internodes 1-6 MAP. Best combination treatment showed on good drainageand maximum land cultivation.Keywords: drainage, land cultivation, sugar cane